Social capital in strengthening the value of gotong royong cooperation through the Sedekah Laut tradition in Munjungagung Village Tegal Regency - Azarine, Bertha Thea Cyrilla; Wijayanti, Tutik (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2026)
This study aims to analyze the formation and interaction of social capital elements in the Sedekah Laut tradition in Mujungagung Village, Tegal Regency, as a mechanism for strengthening mutual cooperation among coastal communities. The study employed a qualitative case study design. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles and Huberman interactive model within the theoretical framework of Robert D. Putnam’s social capital. The research findings indicate that the Sedekah Laut tradition functions as a space for the reproduction of social capital through the internalization of social norms, the development of trust, and the strengthening of social networks among residents. Social norms shape collective expectations regarding the obligation to participate; trust minimizes uncertainty in cooperation; and social networks facilitate coordination and the division of roles. The interaction of these three elements produces repeated collective actions and reinforces the practice of mutual aid in a sustainable manner. These findings confirm that local traditions function not only as cultural rituals but also as social mechanisms that maintain the cohesion and solidarity of coastal communities.   Penelitian ini bertujuan menganalisis pembentukan dan interaksi unsur-unsur modal sosial dalam tradisi Sedekah Laut di Desa Munjungagung, Kabupaten Tegal sebagai mekanisme penguatan nilai Gotong Royong masyarakat pesisir. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman dengan kerangka teori modal sosial Robert D. Putnam. Hasil penelitian menunjukkan bahwa tradisi Sedekah Laut berfungsi sebagai ruang reproduksi modal sosial melalui internalisasi norma sosial, tumbuhnya kepercayaan (trust), serta penguatan jaringan sosial antarwarga. Norma sosial membentuk ekspektasi kolektif mengenai kewajiban partisipasi, kepercayaan meminimalkan ketidakpastian dalam kerja sama, sedangkan jaringan sosial memfasilitasi koordinasi dan pembagian peran. Interaksi ketiga unsur tersebut menghasilkan tindakan kolektif yang berulang dan memperkuat praktik Gotong Royong secara berkelanjutan. Temuan ini menegaskan bahwa tradisi lokal tidak hanya berfungsi sebagai ritual budaya, tetapi juga sebagai mekanisme sosial yang menjaga kohesi dan solidaritas masyarakat pesisir.